Spark plug

By using iridium, platinum, and tantalum in specific ratios, the spark plug achieves improved wear resistance, addressing the wear issues caused by higher currents and voltages in internal combustion engines.

JP7613316B2Active Publication Date: 2025-01-15DENSO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021134661
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-20
Publication Date
2025-01-15
Estimated Expiration
2041-08-20

AI Technical Summary

Technical Problem

Spark plugs experience increased wear due to higher currents and voltages required for improved internal combustion engine performance, necessitating enhanced wear resistance.

Method used

The spark plug is constructed with discharge sections made of a material containing iridium, platinum, and tantalum, with specific weight percentages ranging from 5% to 30% for platinum and 0.3% to 7.5% for tantalum, to enhance wear resistance.

Benefits of technology

The specified material composition significantly reduces wear on discharge sections, ensuring stable spark discharge over extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613316000001
    Figure 0007613316000001
  • Figure 0007613316000002
    Figure 0007613316000002
  • Figure 0007613316000003
    Figure 0007613316000003
Patent Text Reader

Abstract

To provide an ignition plug with improved wear resistance.SOLUTION: An ignition plug 10 comprises a discharge chip 31 and a discharge chip 61 facing the discharge chip 31. At least one of the discharge chip 31 and the discharge chip 61 is made of material containing iridium, platinum, and tantalum. The content of platinum in the material is in the range of 5 wt.% to 30 wt. %, and the content of tantalum in the material is in the range of 0.3 wt.% to 7.5 wt. %.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to spark plugs. [Background technology]

[0002] For example, an internal combustion engine mounted on a vehicle is provided with a spark plug for igniting fuel. The spark plug has a center electrode and a ground electrode, and ignites fuel by generating a spark discharge between these electrodes.

[0003] In the portion of the center electrode where the spark discharge occurs and in the portion of the ground electrode where the spark discharge occurs, the components are consumed due to the spark discharge. The following Patent Document 1 describes how the center electrode and one or both of the ground electrodes are made of a material containing platinum in iridium, thereby suppressing the consumption of the components. The following Patent Document 1 also describes how a discharge tip is made of a material containing platinum in iridium, and the discharge tip is configured by joining the center electrode to one or both of the ground electrodes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-298083 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, spark plugs have become higher in current and voltage in order to increase the power output of internal combustion engines and improve fuel efficiency, etc. This has created a demand for spark plugs to have even higher wear resistance.

[0006] SUMMARY OF THE DISCLOSURE An object of the present disclosure is to provide a spark plug with improved wear resistance. [Means for solving the problem]

[0007] The spark plug (10) according to the present disclosure includes a first discharge portion (31) and a second discharge portion (61) facing the first discharge portion. At least one of the first discharge portion and the second discharge portion is made of a material containing iridium, platinum, and tantalum. The platinum content of the material is within a range of 5% to 30% by weight, and the tantalum content of the material is within a range of 0.3% to 7.5% by weight.

[0008] In the spark plug having the above configuration, the platinum and tantalum contents in the material of at least one of the first and second discharge parts are set within the above ranges, so that wear of the parts where spark discharge occurs can be suppressed more than ever before. Note that the "first discharge part" and "second discharge part" above may be the center electrode and ground electrode themselves, or may be discharge tips joined to the center electrode and ground electrode, respectively. In either case, the parts facing each other across the discharge gap correspond to the "first discharge part" and "second discharge part" above, respectively. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide an ignition plug with improved wear resistance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing the configuration of an ignition plug according to a first embodiment. [Diagram 2] FIG. 2 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the first embodiment. [Diagram 3] FIG. 3 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the second embodiment. [Figure 4] FIG. 4 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the second embodiment. [Diagram 5] FIG. 5 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the second embodiment. [Figure 6] FIG. 6 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the third embodiment. [Figure 7] FIG. 7 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the third embodiment. [Figure 8] FIG. 8 is a diagram showing the relationship between the material of the discharge tip and the wear rate of the spark plug according to the third embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the present embodiment will be described with reference to the accompanying drawings. In order to facilitate understanding of the description, the same components in each drawing are denoted by the same reference numerals as much as possible, and duplicated description will be omitted.

[0012] The configuration of an ignition plug 10 according to a first embodiment will be described with reference to Fig. 1. In Fig. 1, a cross section of the ignition plug 10 taken along a plane including a central axis CX (described later) is shown on the left side. However, among the components constituting the ignition plug 10, the center electrode 30 and the terminal fitting 40 are shown on the left side, rather than in cross section, in their respective external appearances.

[0013] The ignition plug 10 is a device provided in each cylinder of an internal combustion engine (not shown) for igniting fuel in the combustion chamber of the cylinder. The ignition plug 10 includes an insulator 20, a center electrode 30, a terminal metal fitting 40, a metal shell 50, and a ground electrode 60.

[0014] The insulator 20 is a cylindrical member made of an insulating material such as alumina. An axial hole 200 is formed in the insulator 20. The axial hole 200 is a through hole formed to pass through the insulator 20 along its central axis. The central axis of the axial hole 200 coincides with the central axis of the insulator 20. The central axis of the axial hole 200 is hereinafter also referred to as the "central axis CX." In a cross section of the insulator 20 cut perpendicularly to the central axis CX, the shape of the axial hole 200 is circular.

[0015] The center electrode 30 is a metal member held by the insulator 20 at a position that is one end of the axial hole 200 along the central axis CX (the lower end in FIG. 1). The center electrode 30 is a rod-shaped member, most of which is disposed inside the axial hole 200. A part of the center electrode 30 protrudes from the axial hole 200 to the outside of the insulator 20, and a discharge tip 31 is attached to the tip of the protruding part.

[0016] The terminal fitting 40 is a metal member held by the insulator 20 at a position that is the other end of the axial hole 200 along the central axis CX (the upper end in FIG. 1). The terminal fitting 40 is a rod-shaped member, most of which is disposed inside the axial hole 200. A part of the terminal fitting 40 protrudes from the axial hole 200 to the outside of the insulator 20. This protruding part serves as an electrode terminal to which a voltage is applied from an external power source (not shown).

[0017] In the following, the side of the insulator 20 where the center electrode 30 is attached along the central axis CX is also referred to as the "front end side." In the following, the side of the insulator 20 where the terminal fitting 40 is attached along the central axis CX is also referred to as the "rear end side."

[0018] A resistor 71 is disposed in the axial hole 200 between the terminal metal fitting 40 and the center electrode 30. The resistor 71 is a member disposed to adjust the electrical resistance of the electrical path from the terminal metal fitting 40 to the center electrode 30. The resistor 71 is formed of a material in which a predetermined amount of carbon powder is added to powdered glass and zirconia. The electrical resistance of the resistor 71 is adjusted by the amount of carbon added. By disposing the resistor 71 in the electrical path from the terminal metal fitting 40 to the center electrode 30, the generation of electromagnetic noise caused by the spark discharge of the ignition plug 10 is suppressed. The resistor 71 and the center electrode 30 are electrically connected via a conductive seal layer 72. Similarly, the terminal metal fitting 40 and the resistor 71 are electrically connected via a conductive seal layer 73. Both of the conductive seal layers 72 and 73 are layers having electrical conductivity formed of a material in which copper powder is added to powdered glass.

[0019] The metal shell 50 is a tubular member provided so as to cover a portion of the insulator 20 from the outer periphery side. The metal shell 50 is entirely formed of metal. The metal shell 50 is fixed to the insulator 20 by crimping, and holds the insulator 20 in this state. The metal shell 50 has a fitting portion 52, a flange portion 55, and an insertion portion 56.

[0020] The fitting portion 52 is a portion that is fitted with a tool such as a plug wrench when the spark plug 10 is attached to an internal combustion engine. The shape of the fitting portion 52 when viewed along the central axis CX is, for example, hexagonal.

[0021] The flange portion 55 is a portion that comes into contact with the outer surface of the internal combustion engine via the gasket GK when the spark plug 10 is attached to the internal combustion engine. The flange portion 55 is provided at a position that is closer to the tip side than the fitting portion 52, and protrudes toward the outer periphery.

[0022] The insertion portion 56 is a portion further toward the tip side than the flange portion 55, and is a portion to be inserted into an insertion hole (not shown) formed in an internal combustion engine. A male screw 561 is formed on the outer circumferential surface of the insertion portion 56. When the spark plug 10 is attached to the internal combustion engine, the fitting portion 52 rotates about the central axis CX due to the force received from a tool. As a result, a female screw formed on the inner circumferential surface of the insertion hole and the male screw 561 of the insertion portion 56 are screwed together. As a result, the spark plug 10 is fastened and fixed to the internal combustion engine. When the spark plug 10 is attached to the internal combustion engine, the potential of the metallic shell 50 becomes the same ground potential as that of the internal combustion engine.

[0023] The ground electrode 60 is a metal member formed to extend from the tip end of the metallic shell 50 toward the tip side. The ground electrode 60 is bent, and a part of it faces the discharge tip 31 of the center electrode 30 along the central axis CX. The discharge tip 61 is attached to the part of the ground electrode 60 facing the discharge tip 31. The gap formed between the mutually facing discharge tips 61 and 31 is a discharge gap GP where spark discharge occurs.

[0024] 1, inside the fitting portion 52, an annular space SP is formed between the outer circumferential surface of the insulator 20 and the inner circumferential surface of the metallic shell 50. The annular space SP is an annular space formed to surround the central axis CX.

[0025] The annular space SP is filled with a talc material TC, which is powdered talc. The talc material TC increases the impact resistance of the spark plug 10 when it is installed in the internal combustion engine, and also serves to prevent gases from the internal combustion engine from leaking out to the rear end side.

[0026] A first annular member 80 is disposed at a position of the annular space SP that is the end on the leading end side (i.e., the center electrode 30 side) along the central axis CX. A second annular member 90 is disposed at a position of the annular space SP that is the end on the rear end side (i.e., the opposite side to the center electrode 30) along the central axis CX. Both of these are annular members formed to surround the central axis CX, and are formed of a hard metal material such as carbon steel. The first annular member 80 and the second annular member 90 are members for preventing leakage of the talc material TC from the annular space SP.

[0027] When the internal combustion engine is in operation, a pulsed high voltage is applied between the terminal fitting 40 of the spark plug 10 and the body of the internal combustion engine. This high voltage is applied between the opposing discharge tips 61 and 31, causing a spark discharge in the discharge gap GP. The discharge tip 31 corresponds to the "first discharge portion" in this embodiment. The discharge tip 61 corresponds to the "second discharge portion" in this embodiment.

[0028] However, when a spark discharge occurs in the discharge gap GP, the parts that are the starting points of the spark discharge (the discharge tip 61 and the discharge tip 31 in this embodiment) wear out over time. Such wear of parts occurs when some of the material components become hot due to the spark discharge and evaporate, or when some of the material becomes brittle and breaks away. When the discharge tip 31 and other parts wear out, the size of the discharge gap GP changes, and spark discharge no longer occurs stably. For this reason, in order to operate the ignition plug 10 stably over a long period of time, it is necessary to improve the wear resistance of the discharge tip 31 and other parts.

[0029] Therefore, in the spark plug 10 according to this embodiment, the material of the discharge tip 31 is devised to improve wear resistance. The same material as in the past can be used for the material of the discharge tip 61. However, the material of the discharge tip 31 described below may be used for the material of the discharge tip 61. That is, it is sufficient that at least one of the discharge tip 31 and the discharge tip 61 is made of the material described below. Also, in a configuration in which the discharge tip 31 and the discharge tip 61 are not provided and the center electrode 30 and the ground electrode 60 directly face each other across the discharge gap GP, it is sufficient that at least one of the center electrode 30 and the ground electrode 60 is made of the material described below.

[0030] The discharge tip 31 of the present embodiment is made of a material containing iridium (Ir), platinum (Pt), and tantalum (Ta), and the content of each of these elements is adjusted to fall within a predetermined range.

[0031] 2 shows the results of a wear resistance test conducted by the present inventors. In this wear resistance test, the spark plug 10 to be tested was attached to an internal combustion engine, and the engine was operated continuously for 50 hours at a rotation speed of 5600 rpm, after which the amount of reduction in the volume of the discharge tip 31 was measured. The internal combustion engine used was a four-cylinder internal combustion engine with a total displacement of 2000 cc.

[0032] As the material of the discharge tip 31, (1) a plurality of materials in which the platinum content is set to 30% by weight and the tantalum content is changed from 0% by weight to 10% by weight were used. Similarly, (2) a plurality of materials in which the platinum content is set to 20% by weight and the tantalum content is changed from 0% by weight to 10% by weight, (3) a plurality of materials in which the platinum content is set to 10% by weight and the tantalum content is changed from 0% by weight to 10% by weight, and (4) a plurality of materials in which the platinum content is set to 5% by weight and the tantalum content is changed from 0% by weight to 10% by weight were used to carry out the above wear resistance test. In addition, in each material, iridium was used for the remainder other than platinum and tantalum.

[0033] FIG. 2 shows the test results using each of the above materials (1) to (4) as graphs. The horizontal axis of each graph in FIG. 2 represents the tantalum content (weight %) in the material. The vertical axis of each graph in FIG. 2 represents the wear ratio. The "wear ratio" is a value that represents the volume reduction amount of each sample as a ratio when the volume reduction amount of a sample with a tantalum content of 0 weight % is set to 1. When the wear ratio is smaller than 1, it means that the addition of tantalum has reduced the wear amount of the discharge tip 31. When the wear ratio is larger than 1, it means that the addition of tantalum has increased the wear amount of the discharge tip 31.

[0034] As shown in Figure 2, it was confirmed that in all samples, while the tantalum content was small, the wear rate decreased as the tantalum content increased. However, after the tantalum content exceeded a certain amount, the wear rate increased as the tantalum content increased, and it was confirmed that when the tantalum content exceeded approximately 8 wt%, the wear rate became greater than 1 in all samples.

[0035] 2 is a range R01 in which the tantalum content in the material is 0.3% by weight or more and 7.5% by weight or less. If the tantalum content falls within the range R01, the effect of making the wear ratio smaller than 1, that is, the effect of suppressing the amount of wear of the discharge tip 31, can be reliably achieved.

[0036] 2 is a range included inside the range R01, and is a range in which the tantalum content in the material is 1% by weight or more and 5% by weight or less. If the tantalum content falls within the range R02, the above-mentioned effects can be more effectively achieved.

[0037] The melting point of tantalum is higher than the melting points of the other components, iridium and platinum. Therefore, if tantalum, a high melting point material, is contained in the discharge tip 31, the phenomenon of molten metal scattering accompanying spark discharge is suppressed, and it is considered that this suppresses wear of the discharge tip 31. However, if the tantalum content is greater than 5%, tantalum begins to segregate at the grain boundaries of the material, causing the material to tend to become brittle. Therefore, the wear ratio increases with the increase in the tantalum content thereafter, and it is considered that the wear ratio becomes greater than 1 when the tantalum content exceeds approximately 8% by weight.

[0038] Platinum is known as an element that suppresses the volatilization of iridium due to its oxidation. However, since the melting point of platinum is lower than that of iridium, if the content of iridium is too large, the material is more likely to scatter due to melting. The inventors have confirmed that when the content of platinum in the material is greater than 30% by weight, the wear ratio exceeds 1. They have also confirmed that when the content of platinum in the material is less than 5% by weight, the effect of reducing the wear ratio is hardly exerted. For this reason, it is preferable that the content of platinum in the material is within the range of 5% by weight to 30% by weight, as in the above samples.

[0039] Based on the above test results, in the spark plug 10 according to this embodiment, the wear resistance is improved by forming the discharge tip 31 using a material containing iridium, platinum, and tantalum, with the platinum content being within the range of 5% to 30% by weight and the tantalum content being within the range of 0.3% to 7.5% by weight (preferably within the range of 1% to 5% by weight). As described above, this material may be used as the material for the discharge tip 61. In order to achieve the effect of improving the wear resistance, it is sufficient that at least one of the parts facing each other across the discharge gap GP is formed from the above material.

[0040] The second embodiment will be described. This embodiment differs from the first embodiment in the material of the discharge tip 31. The discharge tip 31 in this embodiment is formed using a material that further contains an additive material in addition to iridium, platinum, and tantalum. In this embodiment, nickel (Ni) is used as the additive material. Note that chromium (Cr) or cobalt (Co) may be used as the additive material, or a material that is a mixture of two or three of nickel, cobalt, and chromium may be used. In other words, a material composed of one or more elements of nickel, chromium, and cobalt may be used as the additive material.

[0041] The results of the wear resistance test conducted by the present inventors to confirm the effect of adding the above-mentioned additive material are shown in Figures 3, 4, and 5. The method of this wear resistance test is the same as the method of the wear resistance test described in the first embodiment.

[0042] As the material of the discharge tip 31, (1) a plurality of materials were used in which the platinum content was a predetermined amount (described later), the tantalum content was 0.3 weight percent, and the nickel content was changed from 0 weight percent to 5 weight percent. Similarly, (2) a plurality of materials in which the platinum content was a predetermined amount, the tantalum content was 3 weight percent, and the nickel content was changed from 0 weight percent to 5 weight percent, and (3) a plurality of materials in which the platinum content was a predetermined amount, the tantalum content was 8 weight percent, and the nickel content was changed from 0 weight percent to 5 weight percent, were used for the above wear resistance test. In addition, in each material, iridium was used for the remainder other than platinum, tantalum, and nickel.

[0043] Figure 3 shows, as a graph, the test results for each of the above materials (1) to (3) when the platinum content is 5% by weight, i.e., the "predetermined amount". Figure 4 shows, as a graph, the test results for each of the above materials (1) to (3) when the platinum content is 10% by weight. Figure 5 shows, as a graph, the test results for each of the above materials (1) to (3) when the platinum content is 30% by weight.

[0044] As shown in Figures 3, 4, and 5, it was confirmed that in all samples, as long as the content of nickel, which is an added material, was small, the wear ratio decreased as the nickel content increased. However, after the nickel content exceeded a certain amount, the wear ratio increased as the nickel content increased, and it was confirmed that when the nickel content exceeded approximately 4 wt%, the wear ratio became greater than 1 in all samples.

[0045] 3, 4, and 5, the nickel content in the material is 0.3% by weight or more and 3% by weight or less in the range R11. If the nickel content falls within the range R11, the effect of making the wear ratio smaller than 1, that is, the effect of suppressing the wear of the discharge tip 31, can be reliably achieved.

[0046] 3, 4, and 5, the range R12 is included within the range R11, and is a range in which the nickel content in the material is 0.5% by weight or more and 1.5% by weight or less. If the nickel content falls within the range R12, the above-mentioned effects can be more effectively achieved.

[0047] 3, 4, and 5 show an example in which the additive material is nickel, but the inventors have confirmed that the same results are obtained when chromium and cobalt are used as the additive material. The inventors have also confirmed that the same results are obtained when a material in which two or three of nickel, cobalt, and chromium are mixed is used as the additive material. In either case, the content of the additive material in the material of the discharge tip 31 is preferably within a range R11 of 0.3% by weight or more and 3% by weight or less, and more preferably within a range R12 of 0.5% by weight or more and 1.5% by weight or less. The reason that the same effect is obtained when nickel, cobalt, and chromium are used as the additive material is believed to be because they are elements of the same group.

[0048] Nickel, cobalt, and chromium each have a low free energy and are more easily oxidized than iridium. Therefore, when these are added as additive materials to the material of the discharge tip 31, the phenomenon that iridium is oxidized and separated from the discharge tip 31 is suppressed, and it is considered that the wear resistance of the discharge tip 31 is improved. However, the melting points of nickel, cobalt, and chromium are lower than the melting point of iridium. Therefore, when the content of the additive material in the material of the discharge tip 31 is greater than 1.5% by weight, the phenomenon that molten metal scatters due to spark discharge is likely to occur. Therefore, the wear ratio increases as the content of the additive material increases, and it is considered that when the content of the additive material exceeds approximately 4% by weight, the wear ratio becomes greater than 1.

[0049] The inventors have confirmed that even when an additive material is added as in this embodiment, if the platinum content in the material is greater than 30% by weight, the wear ratio exceeds 1. In addition, they have also confirmed that if the platinum content in the material is less than 5% by weight, the effect of reducing the wear ratio is hardly exhibited. For this reason, it is preferable that the platinum content in the material is within the range of 5% to 30% by weight, as in the first embodiment. The same applies to the tantalum content in the material, and the inventors have confirmed that it is preferable to keep the tantalum content in the same range as in the first embodiment in the configuration of this embodiment.

[0050] Based on the above test results, in the spark plug 10 according to the present embodiment, the discharge tip 31 is formed using a material containing iridium, platinum, and tantalum, with the platinum content being within the range of 5% by weight to 30% by weight and the tantalum content being within the range of 0.3% by weight to 7.5% by weight (preferably within the range of 1% by weight to 5% by weight), thereby enhancing the wear resistance of the discharge tip 31. This is the same as in the first embodiment. In the present embodiment, the material of the discharge tip 31 further contains an additive material composed of one or more elements of nickel, chromium, and cobalt, and the content of the additive material is within the range of 0.3% by weight to 3% by weight (preferably within the range of 0.5% by weight to 1.5% by weight), thereby further enhancing the wear resistance of the discharge tip 31.

[0051] As in the first embodiment, the above material may be used as the material of the discharge tip 61. In order to achieve the effect of further improving wear resistance, at least one of the parts facing each other across the discharge gap GP may be made of the above material.

[0052] A third embodiment will be described. This embodiment differs from the first embodiment in the material of the discharge tip 31. The discharge tip 31 in this embodiment is formed using a material containing an additive material in addition to iridium, platinum, and tantalum, as in the second embodiment. In this embodiment, rhodium (Rh) is used as the additive material. Note that ruthenium (Ru) may be used as the additive material, or a material containing both rhodium and ruthenium may be used. In other words, a material composed of one or more elements of rhodium and ruthenium may be used as the additive material.

[0053] The results of the wear resistance test conducted by the present inventors to confirm the effect of adding the above-mentioned additive material are shown in Figures 6, 7, and 8. The method of this wear resistance test is the same as the method of the wear resistance test described in the first embodiment.

[0054] As the material of the discharge tip 31, (1) a plurality of materials were used in which the platinum content was a predetermined amount (described later), the tantalum content was 0.3% by weight, and the rhodium content was changed from 0% by weight to 20% by weight. Similarly, (2) a plurality of materials in which the platinum content was a predetermined amount, the tantalum content was 3% by weight, and the rhodium content was changed from 0% by weight to 20% by weight, and (3) a plurality of materials in which the platinum content was a predetermined amount, the tantalum content was 8% by weight, and the rhodium content was changed from 0% by weight to 20% by weight, were used for the above wear resistance test. In addition, in each material, iridium was used for the remainder other than platinum, tantalum, and rhodium.

[0055] Figure 6 shows a graph of the test results using each of the above materials (1) to (3) when the platinum content is 5% by weight, i.e., the "predetermined amount". Figure 7 shows a graph of the test results using each of the above materials (1) to (3) when the platinum content is 10% by weight. Figure 8 shows a graph of the test results using each of the above materials (1) to (3) when the platinum content is 30% by weight.

[0056] As shown in Figures 6, 7, and 8, it was confirmed that in all samples, as long as the content of rhodium, an additive material, was small, the consumption ratio decreased as the rhodium content increased. However, after the rhodium content exceeded a certain amount, the consumption ratio increased as the rhodium content increased, and it was confirmed that when the rhodium content exceeded approximately 17 wt%, the consumption ratio became greater than 1 in all samples.

[0057] 6, 7, and 8, the rhodium content in the material is 0.1% by weight or more and 15% by weight or less in the range R21. If the rhodium content falls within the range R21, the effect of making the wear ratio smaller than 1, that is, the effect of suppressing the wear of the discharge tip 31, can be reliably achieved.

[0058] 6, 7, and 8 is a range included inside range R21, in which the rhodium content in the material is 0.3% by weight or more and 5% by weight or less. If the rhodium content falls within range R22, the above-mentioned effects can be more effectively achieved.

[0059] 6, 7, and 8 show an example in which rhodium is used as the additive material, but the inventors have confirmed that the same results are obtained when ruthenium is used as the additive material. The inventors have also confirmed that the same results are obtained when a mixture of rhodium and ruthenium is used as the additive material. In either case, the content of the additive material in the material of the discharge tip 31 is preferably within a range R21 of 0.1% by weight or more and 15% by weight or less, and more preferably within a range R22 of 0.3% by weight or more and 5% by weight or less. The reason that the same effect is obtained when either rhodium or ruthenium is used as the additive material is believed to be because they are elements of the same group.

[0060] Rhodium and ruthenium each have a low free energy and are more easily oxidized than iridium. Therefore, when these are added as additive materials to the material of the discharge tip 31, the phenomenon that iridium is oxidized and separated from the discharge tip 31 is suppressed, and it is considered that the wear resistance of the discharge tip 31 is improved. However, the melting points of rhodium and ruthenium are lower than the melting point of iridium. Therefore, when the content of the additive material in the material of the discharge tip 31 is greater than 5% by weight, the phenomenon that molten metal scatters due to spark discharge is likely to occur. Therefore, the wear ratio increases as the content of the additive material increases, and it is considered that when the content of the additive material exceeds approximately 17% by weight, the wear ratio becomes greater than 1.

[0061] The inventors have confirmed that even when an additive material is added as in this embodiment, if the platinum content in the material is greater than 30% by weight, the wear ratio exceeds 1. In addition, they have also confirmed that if the platinum content in the material is less than 5% by weight, the effect of reducing the wear ratio is hardly exhibited. For this reason, it is preferable that the platinum content in the material is within the range of 5% to 30% by weight, as in the first and second embodiments. The same applies to the tantalum content in the material, and the inventors have confirmed that it is preferable that the tantalum content in the configuration of this embodiment is within the same range as in the first embodiment.

[0062] Based on the above test results, in the spark plug 10 according to the present embodiment, the discharge tip 31 is formed using a material containing iridium, platinum, and tantalum, with the platinum content being within the range of 5% by weight to 30% by weight and the tantalum content being within the range of 0.3% by weight to 7.5% by weight (preferably within the range of 1% by weight to 5% by weight), thereby enhancing the wear resistance of the discharge tip 31. This is the same as in the first embodiment. In the present embodiment, the material of the discharge tip 31 further contains an additive material composed of one or more elements of rhodium and ruthenium, and the content of the additive material is within the range of 0.1% by weight to 15% by weight (preferably within the range of 0.3% by weight to 5% by weight), thereby further enhancing the wear resistance of the discharge tip 31.

[0063] As in the first embodiment, the above material may be used as the material of the discharge tip 61. In order to achieve the effect of further improving wear resistance, at least one of the parts facing each other across the discharge gap GP may be made of the above material.

[0064] The present embodiment has been described above with reference to specific examples. However, the present disclosure is not limited to these specific examples. Any design modifications made by a person skilled in the art to these specific examples are also included within the scope of the present disclosure as long as they have the features of the present disclosure. The elements of each of the above-mentioned specific examples and their arrangements, conditions, shapes, etc. are not limited to those exemplified and can be changed as appropriate. The combination of each of the elements of each of the above-mentioned specific examples can be changed as appropriate as long as no technical contradiction occurs. [Explanation of symbols]

[0065] 10: Spark plug 31,61: Discharge tip

Claims

1. A first discharge section (31); A second discharge portion (61) facing the first discharge portion, At least one of the first discharge portion and the second discharge portion is made of a material including iridium, platinum, and tantalum, the platinum content of the material is in the range of 5% to 30% by weight; the tantalum content of the material is in the range of 0.3% to 7.5% by weight; the material further comprises an additive material comprised of one or more of the elements nickel, chromium, and cobalt; A spark plug, wherein the content of the additive material in the material is within a range of 0.3% to 3% by weight.

2. 2. The spark plug of claim 1, wherein said tantalum content of said material is in the range of 1% to 5% by weight.

3. 3. The spark plug according to claim 1, wherein the content of said additive material in said material is within a range of 0.5% to 1.5% by weight.

4. A first discharge section (31); A second discharge portion (61) facing the first discharge portion, At least one of the first discharge portion and the second discharge portion is made of a material including iridium, platinum, and tantalum, the platinum content of the material is in the range of 5% to 30% by weight; the tantalum content of the material is in the range of 0.3% to 7.5% by weight; the material further comprises an additive material comprised of one or more of the elements rhodium and ruthenium; A spark plug, wherein the content of the additive material in the material is within a range of 0.1% by weight to 15% by weight.

5. 5. The spark plug of claim 4, wherein said tantalum content of said material is in the range of 1% to 5% by weight.

6. 6. The spark plug according to claim 4, wherein the content of said additive material in said material is within a range of 0.3% by weight to 5% by weight.

Citation Information

Patent Citations

  • Spark plug for internal combustion engine

    JP1997298083A

  • Electrode materials for spark plugs

    JP2013512551A